1993
DOI: 10.1177/41.10.8245408
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin in normal lung tissue of newborn mammals: immunocytochemical distribution and co-localization with serotonin and calcitonin gene-related peptide.

Abstract: We demonstrated immunoreactivity for endothelins (ET)-1, -2, and -3 and for the precursor, big-ET-1, in the pulmonary &se neuroendocrine system (PDNES) of newbom cat, rat, hamster, and mouse. ET-& positive neuroepithelial bodies (NEB) were numerous in the intrapulmonary airways and the alveolar parenchyma. Single neuroendocrine c e l l s (NEC) were less often labeled and mainly localized in the larger bronchi. ET+rea&ve neuronal elements were rarely observed. The intensity and number of iaununostained NEB were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…As a first step in studying the phylogeny of the NE (paraneuronal) cells of the fish gill, results from our laboratory indicated that many bioactive substances, including endothelin, are also typical markers of the NE cell system of mammalian airways (Dey et al, 1981;Cutz et al, 1984;Dey & Hoffpanir, 1986;Lauweryns et al, 1986;Seldeslagh & Lauweryns, 1993;Zaccone et al, 1996Zaccone et al, , 1998. Specific cytokeratins and calcium-binding proteins (CaBPs) are also assumed to be possible markers of these cells.…”
Section: Introductionmentioning
confidence: 92%
“…As a first step in studying the phylogeny of the NE (paraneuronal) cells of the fish gill, results from our laboratory indicated that many bioactive substances, including endothelin, are also typical markers of the NE cell system of mammalian airways (Dey et al, 1981;Cutz et al, 1984;Dey & Hoffpanir, 1986;Lauweryns et al, 1986;Seldeslagh & Lauweryns, 1993;Zaccone et al, 1996Zaccone et al, , 1998. Specific cytokeratins and calcium-binding proteins (CaBPs) are also assumed to be possible markers of these cells.…”
Section: Introductionmentioning
confidence: 92%
“…To our knowledge this peptide is reported for the first time in the diffuse neuroendocrine system of the respiratory organs of lower vertebrates. However, endothelin-like immunoreactivity was previously reported in NEBs of mammalian lung (Seldeslagh and Lauweryns, 1993).…”
Section: Neuroendocrine Markersmentioning
confidence: 88%
“…Furthermore, an often underestimated reason for such discrepancies might derive from crossreacting antibodies. Accordingly, only few authors are critical concerning specificity of ET antibodies (Saito et al 1991;Seldeslagh and Lauweryns 1993;Svane et al 1993). For instance, Yanagisawa's group (Saito et al 1991) discussed their results with great care: "since the antibodies might have crossreacted with unknown substances, the immunoreactive material was termed 'endothelin-like' in the present study."…”
Section: Introductionmentioning
confidence: 95%